The numerical reckoning of modified proximal point methods for minimization problems in non-positive curvature metric spaces. Issue 1 (1st February 2020) - Thounthong, Phatiphat; Pakkaranang, Nuttapol; Cho, Yeol Je; Kumam, Wiyada; Kumam, Poom
ABSTRACT: In this paper, we introduce a new modified proximal point algorithm for nonexpansive mappings in non-positive curvature metric spaces and also we prove the sequence generated by the proposed algorithms converges to a common solution between minimization problem and fixed point problem. Moreover, we give some numerical examples to illustrate our main results, that is, our algorithm is more efficient than the algorithm of Cholamjiak et al. and others.